Frechet Lie Algebroids and Their Cohomology - Eftekharinasab, Kaveh (Armenian Journal of Mathematics, 2016)
We define Lie and Courant algebroids on Frechet manifolds. Moreover, we construct a Dirac structure on the generalized tangent bundle of a Frechet manifold and show that it inherits a Frechet Lie algebroid structure. We show that the Lie algebroid cohomology of the B-cotangent bundle Lie algebroid of a weakly symplectic Frechet manifold M is the Lichnerowicz-Poisson cohomology of M.